RITUAL MANDI PENGANTIN DALAM UPACARA PERKAWINAN ADAT BANJAR DI MARTAPURA KALIMANTAN SELATAN - Widaty, Cucu; Nur, Rahmat (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Marriage according to Banjarese custom in Martapura, Banjar Regency is the business of all parties, both the bride and groom, but is the obligation of both parents, tengganai, formal leaders, and traditional leaders. In Banjar traditional marriage procedures, there is a bridal shower ritual ceremony. The purpose of this study is to describe the implementation of the bridal shower ritual and the meaning contained in the ritual in the Banjar traditional wedding ceremony. The research method used in this study is a qualitative approach. The results of the study found that the bridal shower ceremony aims to purify physically and spiritually because on the next day the bride and groom will carry out one of the sacred tasks in life in the world, namely undergoing marriage mahligai. The bridal shower only purifies the body, but the implied meaning is that the bride and groom are ready to purify themselves physically and mentally. As well as to fortify the bride and groom from various unwanted disturbances. The meaning contained in the bridal shower ritual is that a blessed life has the hope that in carrying out a relationship in the household, happiness is always given. Behaving well in pisit is symbolized by nyiur (coconut). Nyiur has the meaning of the tree of life which is very useful for others. The meaning of living together is symbolized by baras lakatan (glutinous rice) which means a form of hope for the safety of the bride and groom. Habang sugar has a sweet meaning and is red in color, the hope is that everything that is done always bears sweet fruit or has a meaning that the sugar can symbolize a beautiful life that is lived with his life partner. hintalu (egg) has the meaning of a symbol of life as a generational strength which is expected to have a strong future generation and always be useful for others.